Social Learning, Self-Control, Gender, and Variety of Violent Delinquency. Issue 7 (2nd July 2016) - Koon-Magnin, Sarah; Bowers, David; Langhinrichsen-Rohling, Jennifer; Arata, Catalina
ABSTRACT: This study tested the role of social learning and self-control theories in the variety of violent delinquent behaviors engaged in by male and female adolescents ( N = 833). Results of Tobit analyses indicated that neither theory was able to account for the gender gap. Low self-control was significantly associated with an increase in the variety of violent delinquency among females. Among male respondents, those who were more susceptible to peer pressure engaged in fewer types of violent delinquency. We conclude that theories must actively recognize the role of gender to better account for the differences in violent delinquent behavior.